2019
DOI: 10.18203/2394-6040.ijcmph20195070
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical profile of scrub typhus outbreak in a tertiary care centre of central India

Abstract: Background: Scrub typhus is the most common rickettsial infection in the Indian subcontinent with the manifestation ranging from mild symptoms to serious disease with or complication or death. The objective of this study was to study epidemiology and clinical profile of scrub typhus outbreak in a tertiary care centre of central India. Methods: Present study is a record based retrospective study enrolling 173 confirmed positive cases with ELISA test during the period from 1 st August to 31 st December 2018. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This finding is in concordance with the studies conducted by Saha et al and also with the data found by Indian Council of Medical Research. 16,17,18 Fever is the most common symptom reported by the different patients which is similar to other studies. 3,9,19 No mortality was found in the study and all the patients recovered fully from the infection probably because of early diagnosis and increased use of the drug Doxycycline for the treatment of the infection.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is in concordance with the studies conducted by Saha et al and also with the data found by Indian Council of Medical Research. 16,17,18 Fever is the most common symptom reported by the different patients which is similar to other studies. 3,9,19 No mortality was found in the study and all the patients recovered fully from the infection probably because of early diagnosis and increased use of the drug Doxycycline for the treatment of the infection.…”
Section: Discussionsupporting
confidence: 87%
“…Narlawar et al explored cases in central India; the common symptoms were fever, fever with chills, breathlessness, cough, altered sensorium, vomiting and nausea, swelling over feet, headache, gastrointestinal symptoms, urinary symptoms, skin lesions (eschar). Other complications are pancreatitis, ARDS, septicemia, encephalitis, AKI, osteoarthritis, and renal calculi [ 42 ]. Varghese et al highlighted case distribution in south India where ARDS, shock requiring inotropic support, hepatitis, meningoencephalitis, renal failure, invasive ventilation and CNS dysfunction were seen, confirming with IgM ELISA [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…also lately described the clinico-epidemiological profile of 173 outbreak cases over a 5-month period from Central India, most cases being from rural areas, where 17.3% of patients expired despite adequate care. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%